Evaluating the Changes and Impacts of Heritage Building to Small Hotel Building: A Case Study of Bangkok Story Hostel - Chotewit Pongsermpol; Prapatpong Upala (Book Publisher International (a part of SCIENCEDOMAIN International), 2021)
Over the last decade, trends of adaptive reuse of old buildings turned into hotels have been popular in Thailand, especially in Bangkok. Adaptive Reuse Heritage Building converted to the Hotel Building, AR-HB-hotel, effects changes and impacts in several aspects. There have been established criteria for substantial renovation, business investment and assessment of the value of heritage buildings but no concern has been paid to the surrounding community impact. As heritage buildings are worth preserving, their value is one significant issue that we have to consider.Heritage is valued in a variety of ways and the value is driven by different motivations: economic, political, cultural, spiritual, aesthetic. The objective is to study four issues of AR-HB-hotel focused on (1) physical, (2) economic, (3) value changes, and (4) social impacts. The research method is mixed qualitative and quantitative study. ‘Bangkok Story Hostel’ was selected as a representative case for AR-HB-hotel. This small 3-storey heritage hotel is located in a traditional trading district on Songward Street, Sampanthawong district, Bangkok. For the data collection, building history and project background, as well as physical and economic changes were collected from secondary data, surveys, and in-depth interview. Value change and social impact were collected from in-depth interview and questionnaire. The results showed that the level of physical, economic, and value changes of this building rose up, while the level of social impact stays the same or decreased a little less than the level before the renovation. This mixed research may not be generalized wholly to another case with a significantly different context, but the four main approaches for examining physical, economic, value, and social issues and the procedure used in this study can be a guideline for future studies of AR-HB-hotel’ changes and impacts.
Keywords: Cultural Heritage Management and Preservation